Higher Education Research Goes Global - de Wit, Hans (International Higher Education, 2016)
Two recent developments show that higher education research is acquiring a strong global focus: In the first place the creation of the ESRC/HEFCE Centre for Global Higher Education, or CGHE, at the Institute of Education in the United Kingdom, with ten partner institutions around the world; and in the second place the creation of the Group of “Global Centers for International Higher Education Studies”, or GCIHES, in which the Center for International Higher Education collaborates with five other centers in the world, and which has its secretariat at the Pontificia Universidad Católica de Chile in Santiago. These initiatives can be seen as a product of the “Shanghai Statement, The Future of Higher Education: The need for research and training for the higher education enterprise” in 2013. Where higher education research was in the past limited and mainly focused on national and regional aspects, like the sector itself, the shift is now towards international higher education. This is an important development.